Chemical, physicochemical profile and dose-response effect of Hymenaea courbaril essential oil on bacteria - Santos, Wellita Maria dos; Menezes Filho, Antonio Carlos Pereira de; Castro, Carlos Frederico de Souza; Teixeira, Marconi Batista; Soares, Frederico Antônio Loureiro; Porfiro, Cinthia Alves (Brazilian Journal of Science, 2022)
Hymenaea courbaril is a tree species belonging to the genus Hymenaea and family Fabaceae. This study aimed to extract the essential oil from the fruit peel and evaluate the physicochemical characteristics and bacterial activity. The fruits were collected in the municipality of Santa Helena de Goiás, Goiás, Brasil. The bark was crushed and the powder obtained used in the extraction of the essential oil in the Clevenger-type system. The physical-chemical evaluation was performed for organoleptic analysis, refractive index, relative density, optical rotation and solubility in 70% hydroethanolic solution. The chemical profile was evaluated by gas chromatography with a coupled mass emitter. The antibacterial assay was performed in a Petri dish at different oil concentrations and the antibiosis halo (mm) when present was evaluated with the aid of a caliper. The essential oil of the peel of the fruit of H. courbaril was aromatic, clear, slightly aromatic, presenting physicochemical characteristics similar to the several essential oils of plants. It demonstrated a chemical profile rich in molecules and effective antibacterial action.